English Speaking Problems Encountered by ELF Learners of Madrasah Tsanawiyah Sayang-sayang Cakranegara - Sudirman; Tawali (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to find out the problems speaking at Madrasah Tsanawiyah Nurul Yaqien Sayang-sayang Cakranegara, which is located at the P. Diponegoro. The writer uses interviews as a research instrument consisting of 5 students, the writer provides conclusions on the intent and purpose of increasing students interest in speaking. In addition, the student’s main problems in speaking are difficulties in pronunciation, lack of vocabulary so that students show that learning to speak English is not fun. This study would like to suggest that, for English teachers, it is better to encourage them to increase their willingness to communicate well so that their desire to learn and keep practising arises. Regardless of its importance, teaching speaking skills has been underestimated, and the most ELFteachers continue their teaching of speaking skills just as memorization of dialogues or drill repetition. Nevertheless, the modern world requires learners to have communication skills, and English teachers have to teach the ELL (E-language learning system) the necessary skills so that they can develop their speaking skills and perform well in real life situations. Oral skills are completely disregarded in today’s EFLteaching environment, despite the fact that employability is more dependent on communication than technology. Because crucial components of language, such as phonological, morphological, semantic, and syntactic characteristics, have received little attention, it has become major hurdle for ELL to acquire speaking skills among English learners. So far, more concentration has been placed on reading and writing skills